Diet planning model for students in university by using zero-one integer linear programming / Mohamad Fariz Razib... [et al.] - Razib, Mohamad Fariz; M Fuad, Fathy Anith Najihah; Noordin, Naemah (2019)
In recent years, the rate or obesity in Malaysia has been increased since a few years back then including to the students in university. Obesity is a condition where excessive fat accumulated at the level that affect someone's health. Students in university become obesity because they do not know how to manage their money well and eat unhealthy food in their daily menus. Therefore, this study aims to formulate a menu planning model for students with the best nutritional requirement as well as minimizing the cost. The data was collected from students in UiTM Cawangan Negeri Sembilan, Kampus Seremban and have been analyzing by using zero-one integer linear programming. The result obtained satisfies all the objectives of this research since the total cost or food consumed is less than RM 15 per day.